Beyond the milk carton: strategies for creating and allowing a space for engaging with personal narratives from family members about missing persons - Drennan, Lisa (Centre for Film and Media Studies, 2018)
The aim of this study is twofold, firstly to explore various media's coverage of missing children to probe whether they currently include the reflections and personal narratives of family members and loved ones and secondly to propose possible strategies for creating space for such content in the media. The much- publicised case of Madeleine McCann going missing in Portugal in 2007, showed how much power the media still yields and how much awareness can be created if the media choose to cast light on a particular case. But this case also stood out for another reason: many interviews conducted with the family after her disappearance didn't merely contain the facts surrounding her disappearance, they were also heartfelt narratives about the pain and horror that the family were going through. The public were not only made aware of their missing daughter but also of the very real and horrific way her disappearance had punctured their suburban life forever. Very few other cases of missing children have garnered the kind of media attention that allows parents of missing children to reflect in such a way. Most newspapers in South Africa at present barely report a child missing; let a lone create a space for parents to reflect on their loss (Drennan, 2012). News is often considered to be centred around the interests of the élite (Herman and Chomsky 1988) and often certain demographics like race, gender and ethnicity can influence how 'newsworthy' certain crimes or stories are considered to be (Pritchard and Hughes 1997, Gruenewald, Pizarro and Chermak 2009). Although social media allows a flow of information that is immediate (So, 2011), the information is still mostly centred around quick mobilisation of the public to find the missing person in the shortest time possible and doesn't allow a space for family members to reflect or share their experiences. Television plays a vital role by entertaining the viewer with facts and events that engage the audience but not much content can be found that allows the family and friends of the missing person to reflect on their sad and often lonely experience of losing a loved one in such a traumatic way. The existing television formats (fiction and non-fiction) are perhaps not ideal for intimate reflection and sharing emotional responses. By using narrative inquiry and action research while producing my own film about a missing person, I was able to test various fiction and non-fiction programming models. Four cycles of action research helped me to understand and determine what form would be best in order to create a space that would allow for intimate reflection from family members of missing persons. Through a process of trial and error, I found that a documentary form that incorporates inspiration from fiction and non-fiction forms was the most fitting platform to create an intimate space for reflection and sharing (Stubbs 2002; Nichols 2001). By combining these various elements I believe that I was able to make a film that is ethical, sensitive and respectful of my subject; to focus renewed attention on a cold case, while creating space for intimate reflection, something no other medium or platform I studied was able to do.